2022
DOI: 10.1101/2022.01.20.22269601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiomic Body Mass Index signatures in blood reveal clinically relevant population heterogeneity and variable responses to a healthy lifestyle intervention

Abstract: Multiomic profiling is useful in characterizing heterogeneity of both health and disease states. Obesity exerts profound metabolic perturbation in individuals and is a risk factor for multiple chronic diseases. Here, we report a global atlas of cross-sectional and longitudinal changes associated with Body Mass Index (BMI) across 1,100+ blood analytes, as well as their correspondence to host genome and fecal microbiome composition, from a cohort of 1,277 individuals enrolled in a wellness program. Machine learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Including two cohorts of different ages and populations also empowered the identification of biomolecules likely to be stable across generations and populations. This is in line with two longitudinal multi-omics studies that identified stable biomolecules in response to interventions and investigated proteome resistance to weight change [18,19]. Although BMI measurements at blood sampling were similar between the two cohorts (Table 1), both the length of follow-up and the intensity of BMI changes between the two cohorts differed.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Including two cohorts of different ages and populations also empowered the identification of biomolecules likely to be stable across generations and populations. This is in line with two longitudinal multi-omics studies that identified stable biomolecules in response to interventions and investigated proteome resistance to weight change [18,19]. Although BMI measurements at blood sampling were similar between the two cohorts (Table 1), both the length of follow-up and the intensity of BMI changes between the two cohorts differed.…”
Section: Discussionsupporting
confidence: 83%
“…Overall, only a few multi-omics studies quantified biomolecules (i.e., metabolites or proteins) and omics stability in relation to participants' post-intervention weight changes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…There are hurdles associated with translating omic technologies to clinical useincluding cost, technology development, and education (38)-but our results show that their inclusion increases predictive value. Other studies have shown that omic data integrated with clinical labs can yield increased model performance, but these results are for health metrics (15) and not clinically validated tests. Second, the ability to interpret model predictions via a knowledge graph provides a robust framework for the implementation of biomedical digital twins.…”
Section: Discussionmentioning
confidence: 97%
“…In this study we used the Arivale dataset, described in detail in (14,15). Briefly, the Arivale dataset includes longitudinal data from ∼5,000 deeply phenotyped individuals undergoing a wellness program.…”
Section: Dataset Description and Processingmentioning
confidence: 99%
See 1 more Smart Citation